Respuesta :
4x − 1 = −2 (x + 1) ⇒ Given
4x−1=−2x−2⇒ Distributive property (since we've multiplied out -2(x+1))
6x−1=−2 ⇒ Addition or Subtraction Property of Equality (We've added 2x onto the 4x to get 6x)
6x=−1 ⇒ Commutative Property (We've moved -1 to the other side to get the sum -2+1 = -1)
x=−¹/₆ ⇒ Multiplication or Division Property of Equality (We divided both sides by 6)
4x−1=−2x−2⇒ Distributive property (since we've multiplied out -2(x+1))
6x−1=−2 ⇒ Addition or Subtraction Property of Equality (We've added 2x onto the 4x to get 6x)
6x=−1 ⇒ Commutative Property (We've moved -1 to the other side to get the sum -2+1 = -1)
x=−¹/₆ ⇒ Multiplication or Division Property of Equality (We divided both sides by 6)
Answer:
Given
Distributive property
Addition or Subtraction Property of Equality
Addition or Subtraction Property of Equality
Multiplication or Division Property of Equality
Step-by-step explanation:
4x − 1 = −2 (x + 1) Given This is the starting point.
4x−1=−2x−2 Distributive property Distributes the -2 to the (x+1)
6x−1=−2 Addition or Subtraction Property of Equality Adds 2x to both sides
6x=−1 Addition or Subtraction Property of Equality Adds 1 to both sides
x=−¹/₆ Multiplication or Division Property of Equality Divides both sides by 6